Si wire waveguide polarisation‐independent wavelength filter using polarisation rotation Bragg grating. Issue 20 (1st September 2014) - Okayama, H.; Onawa, Y.; Shimura, D.; Takahashi, H.; Miyamura, S.; Yaegashi, H.; Sasaki, H.
Abstract : A polarisation‐independent Bragg grating wavelength filter using polarisation rotation is reported. A rib waveguide Bragg grating structure and second‐order mode are used to generate the polarisation rotation. A device connected to polarisation beam splitter (PBS) to obtain a polarisation‐independent device is fabricated. The measured diffraction wavelength peaks were almost the same for both input polarisations.